Simulation performance analysis of new TCP extensions over hybrid satellite networks - Villorente, Denis F. (2001)
This thesis investigates the performance of new TCP extensions over hybrid satellite networks using a network simulation setup. Three TCP implementations (TCP Reno, TCP Sack, and TCP with FACK) incorporating different TCP loss recovery mechanisms are investigated in order to determine which implementation works best over networks that involve the combination of a satellite link with a terrestrial link as well as networks that involve only terrestrial links. Performance analysis is done to determine which among the TCP implementations tested provide the best throughput and efficiency. According to the results of the study, both SACK and FACK perform better than Reno in all the environments investigated. Based on these results, it is recommended that SACK be adopted for use on hosts using hybrid satellite networks.